Molecular mechanisms of leukemogenesis - D. A. Domninskiy (Онкогематология)
The journal begins to publish a series of lectures for doctors, which is devoted to the molecular mechanisms of leukemia. Modern medicine is on the verge of the emergence of a large number of new generation drugs whose activity is aimed at modulating (activating or suppressing) the functions of certain target molecules that are involved in the processes of leukemia. Such targets can be enzymes, proteins with other (non-enzymatic) functions, genomic DNA, mRNA, or, for example, certain lipid components of cell membranes. It can be expected that such targeted (targeted) therapy will significantly improve the results of the treatment of hematological tumors. However, its application will make fundamental changes in the work of an oncologist. This is due to the fact that rapidly improving methods of molecular diagnostics will make it possible in the near future to detect in patients not only specific for this type of tumor (recurrent) genetic aberrations, but a whole range of genomic disorders. And since the evolution of each specific tumor proceeds according to an “individual” program, there is a high probability that the combination of various aberrations in leukemia cells will also have an individual (patient-specific) character. If at the same time the doctor has a whole set of targeted drugs “at hand”, then this will require him to be able to independently draw up an individual course of therapy for each patient. Therefore, the hematologist must understand the cellular processes, the action of which he is going to modulate with the help of such drugs. For example, to know which of them can and should be used together, and for which drugs the combined use is meaningless or even harmful. In a short series of lectures it is impossible to consider the most important issues of molecular biology and genetics, but the author does not set himself such a task. It is much more important to teach the physician to understand the key mechanisms of interactions between various cellular molecules and how these interactions are disrupted in the presence of oncogenic proteins. There are many tumor-causing target molecules, and the number of mechanisms by which they realize their pathological potential is not so big. Therefore, in the first lectures, the main molecular mechanisms, the disruption of which most often leads to the development of leukemia, will be considered. In subsequent lectures, the main genetic aberrations characteristic of hematological tumors of myeloid and lymphoid origin, as well as targeted drugs used in the treatment of these diseases, will be described. Today there is a large amount of literature on the issues under discussion, we will give links to published reviews, giving preference to works that are in the public domain. Internet access. As a “basic” source, a series of lectures by E.  B. Vladimirskaya “Mechanisms of hematopoiesis and leukemogenesis” published 3 years ago [1] is used, so questions that covered in detail in this work, will not be considered here. Since many references will be given to English-language literature, in this series of lectures widely used international names for proteins and genes will be used, and English names of the main terms will be given, abbreviations will be deciphered and the origin of the names will be explained (where necessary and possible). As an introduction to the etymology of gene names, the material given in Appendix 1 can be considered.